The MAP (Me-As-a-Process) coaching model: a framework for coaching women’s identity work in voluntary career transitions - Snape, Sarah (Frontiers in Psychology, 2024)
Dealing with change and the resulting process of transition is challenging. In today’s workplace, where change and innovation are increasingly a fact of life, too many transitions end in failure, at a high cost to both people and organizations. Interest in the identity work integral to career transition has grown rapidly in recent years and it is now recognized that career transition is more than simply a change in status, salary and role description. It involves social, relational and personal shifts, conscious and unconscious processes, and identity work—agentic, holistic engagement in the shaping and sustaining of who we become. Evidence suggests that specifically addressing identity work in coaching leaders, teams and groups significantly increases the success rate of transitions. And yet topics around identity and identity work are given little prominence in coaching education, leaving many coaches unaware of these basic constructs. This paper presents a new coaching framework, the MAP (Me-As-a-Process) coaching model, to support coaches and their clients as they embark on the process of identity work in voluntary career choices and transitions. It draws on research from my qualitative doctoral study (2021) which identified four stages in the process of women’s identity work in voluntary career change and choice. It synthesizes academic theory, evidence from coaching practice, and findings from 53 women who had recently experienced career choice or change.